Probing into propaganda an analysis and assessment of the Visiting Forces Agreement infomercials - Dungca, Reinier Cruz 1980-
This study seeks to make an assessment and evaluation of the infomercials of the Visiting Agreement in the period 1998-1999. Content and textual analyses are used to assess the strengths and weaknesses of the infomercials as well as the implications and meanings they bear. Five television and radio infomercials are covered, analyzed and evaluated in terms of the characteristics of the presenters, the message delivered, the language and gestures used, and the audio-visual features of the infomercials. Findings show that the VFA infomercials had good endorsers but delivered weak and faulty messages. Language used and audio-visual qualities were also not quite effective. The study points out the weak points of the infomercials, especially the way they underestimate the issue of the VFA and, thus, undermine the purpose of information dissemination.